Thermoplastic polyimide resin and thermoplastic polyimide precursor
A thermoplastic polyimide resin with alicyclic structural units addresses the heat resistance and processability issues of existing polyimides, offering improved performance in optical equipment through enhanced heat resistance and processability.
Patent Information
- Application Number
- JP2023104235
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
Existing polyimide resins used in optical equipment have insufficient heat resistance and poor processability, limiting their performance in high-temperature applications.
A thermoplastic polyimide resin is developed with structural units derived from a tetracarboxylic dianhydride having an alicyclic structure and a diamine represented by a specific formula, enhancing heat resistance and processability.
The new polyimide resin exhibits excellent heat resistance and processability, enabling the production of molded products with high glass transition temperatures and improved light transmittance, suitable for optical equipment.
Smart Images

Figure 2025004507000017 
Figure 2025004507000001 
Figure 2025004507000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic polyimide resin and a thermoplastic polyimide precursor. [Background technology]
[0002] In recent years, with the development of information and communication technology, such as the transition from the fourth generation communication system (4G) to 5G, there is a demand for improved performance of optical devices such as optical transceivers to cope with the increased communication speed and traffic of information handled in data centers. For example, an optical transceiver has an optical module (light receiving element, light emitting element) mounted inside the housing, and the optical module is electrically connected to a circuit board (a board with a driving circuit) via a flexible substrate.
[0003] Polyimide resins are sometimes used for the components of such optical devices. Examples of the polyimide resins include those disclosed in Patent Documents 1 and 2. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 1983 / 000442 [Patent Document 2] JP 2002-293930 A Summary of the Invention [Problem to be solved by the invention]
[0005] To improve the performance of optical devices, polyimide resins that can be used in optical devices are required to have higher heat resistance than ever before. However, the polyimide resins disclosed in Patent Documents 1 and 2 sometimes have insufficient heat resistance or poor processability due to high molding temperatures.
[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a thermoplastic polyimide resin having excellent heat resistance and processability. [Means for solving the problem]
[0007] The present invention provides a thermoplastic polyimide resin having a structural unit derived from a tetracarboxylic dianhydride (A) having an alicyclic structure and a structural unit derived from a diamine (B) represented by the following formula (1). [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R 1 represents a divalent organic group, and m represents an integer of 0 or more.
[0008] The above thermoplastic polyimide resin preferably has a glass transition temperature of 200° C. or higher.
[0009] The thermoplastic polyimide resin is preferably in the form of a powder.
[0010] It is preferable that the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded via a single bond or a linking group.
[0011] The alicyclic structure is preferably a 3- to 6-membered monocyclic structure.
[0012] R in the above formula (1) 1 is preferably a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group.
[0013] The present invention also provides a fibrous thermoplastic polyimide precursor which is a condensation polymer of a tetracarboxylic dianhydride (A) having an alicyclic structure and a diamine (B) represented by the following formula (1). [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R1 represents a divalent organic group, and m represents an integer of 0 or more.
[0014] It is preferable that the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded via a single bond or a linking group.
[0015] The alicyclic structure is preferably a 3- to 6-membered monocyclic structure.
[0016] R in the above formula (1) 1 is preferably a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group.
[0017] The present invention also provides a composition comprising the above thermoplastic polyimide precursor and substantially free of a curing accelerator.
[0018] The present invention also provides a molded product of the above thermoplastic polyimide resin.
[0019] The present invention also provides an optical device comprising the above molded article. Effect of the Invention
[0020] The thermoplastic polyimide resin of the present invention is excellent in heat resistance and processability, and therefore, a molded product of the polyimide resin having excellent heat resistance can be easily obtained. [Brief description of the drawings]
[0021] [Figure 1] 4 shows a graph obtained by measuring the light transmittance of the molded body of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] [Thermoplastic polyimide resin] The thermoplastic polyimide resin of the present invention has a structural unit derived from a tetracarboxylic dianhydride (A) having an alicyclic structure and a structural unit derived from a diamine (B) represented by the following formula (1). In this specification, the structural unit derived from the tetracarboxylic dianhydride (A) having an alicyclic structure may be referred to as the "structural unit (A)" and the structural unit derived from the diamine (B) represented by the following formula (1) may be referred to as the "structural unit (B)". The thermoplastic polyimide resin of the present invention may have only one type of structural unit (A) and one type of structural unit (B), or may have two or more types.
[0023] [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R 1 represents a divalent organic group, and m represents an integer of 0 or more.
[0024] (Tetracarboxylic acid dianhydride (A)) The tetracarboxylic dianhydride (A) is a compound having an alicyclic structure and two carboxylic anhydride skeletons. The alicyclic structure may be a monocyclic structure or a condensed ring structure composed of a plurality of alicyclic rings. When the alicyclic structure is condensed with a ring structure other than the alicyclic structure, such as an aromatic ring structure, the alicyclic structure is considered to be a monocyclic structure. However, when the condensed ring has aromaticity, the alicyclic structure is not considered to be an alicyclic ring. The alicyclic ring constituting the alicyclic structure may be either a saturated aliphatic hydrocarbon ring or an unsaturated aliphatic hydrocarbon ring.
[0025] The number of alicyclic structures in the tetracarboxylic dianhydride (A) is 1 or more, preferably 1 to 5, more preferably 1 to 3, and even more preferably 1. For a condensed ring structure, the number of monocyclic rings constituting the condensed ring structure is calculated as the number of alicyclic structures. For example, a norbornane structure has two alicyclic structures. When the tetracarboxylic dianhydride (A) has two or more alicyclic structures, the alicyclic structures may be the same or different.
[0026] Examples of the monocyclic ring in the monocyclic structure include a cyclopropane ring, a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, a cyclooctane ring, a cyclohexene ring, etc. The monocyclic ring is preferably a 3- to 8-membered ring, more preferably a 3- to 6-membered ring, and further preferably a 5- or 6-membered ring.
[0027] The fused ring in the fused ring structure includes a bridged hydrocarbon ring such as a bicyclic aliphatic hydrocarbon ring or a tricyclic or higher aliphatic hydrocarbon ring. Examples of the bicyclic hydrocarbon ring include a pinane ring, a pinene ring, a bornane ring, a norbornane ring, and a norbornene ring. Examples of the tricyclic or higher aliphatic hydrocarbon ring (a bridged hydrocarbon ring having three or more rings) include a dicyclopentane ring, a dicyclopentene ring, an adamantane ring, a tricyclopentane ring, and a tricyclopentene ring. The number of atoms constituting the fused ring structure is preferably 6 to 12, and more preferably 7 to 10.
[0028] The alicyclic structure may have a substituent, such as a hydrocarbon group having 1 to 4 carbon atoms.
[0029] The tetracarboxylic dianhydride (A) preferably has an aromatic ring structure. When the aromatic ring structure is present, the glass transition temperature of the thermoplastic polyimide resin increases, and the heat resistance tends to improve. The aromatic ring in the aromatic ring structure may be an aromatic hydrocarbon ring or an aromatic heterocycle. The aromatic ring structure may form a condensed ring with the alicyclic structure.
[0030] Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, a phenanthrene ring, an anthracene ring, a fluorene ring, etc. Examples of the aromatic heterocycle include a furan ring, a pyridine ring, etc.
[0031] When the tetracarboxylic dianhydride (A) has an aromatic ring structure, the number of the aromatic ring structures is preferably 1 or more, more preferably 1 to 3, even more preferably 1 to 2, and even more preferably 1. When the number of the aromatic ring structures is 3 or less, the processability of the thermoplastic polyimide resin is more excellent. In addition, the light transmittance of the molded product is more excellent. In addition, for a condensed ring structure, the number of single rings constituting the condensed ring structure is calculated as the number of aromatic ring structures. For example, a naphthalene structure has two aromatic ring structures. When the aromatic ring structure has two or more aromatic ring structures, the respective aromatic ring structures may be the same or different.
[0032] The tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure as a carboxylic acid anhydride skeleton. The alicyclic structure is preferably bonded to at least one of the cyclic acid anhydride structures via a single bond or a linking group. In this case, it is presumed that the rigidity of the molecule of the tetracarboxylic dianhydride (A) is alleviated, and the processability of the thermoplastic polyimide resin is more excellent. The linking group is not particularly limited as long as it is a divalent group, and examples thereof include a divalent organic group, an ether bond, an ester bond, and a carbonyl bond. In addition, the alicyclic structure may form a condensed ring with at least one of the cyclic acid anhydride structures.
[0033] Examples of the divalent organic group include a divalent aliphatic hydrocarbon group which may have a substituent, a divalent alicyclic hydrocarbon group which may have a substituent, a divalent aromatic hydrocarbon group which may have a substituent, a divalent group in which two or more of these are bonded together, and a divalent group in which two or more of these are bonded together via another linking group (such as an ether bond, an ester bond, or a carbonyl bond).
[0034] Examples of the divalent aliphatic hydrocarbon group include linear or branched alkylene groups having 1 to 10 carbon atoms, such as methylene, methylmethylene, dimethylmethylene, ethylene, propylene, and trimethylene groups; linear or branched alkenylene groups having 2 to 10 carbon atoms, such as vinylene, 1-methylvinylene, propenylene, 1-butenylene, 2-butenylene, 1-pentenylene, and 2-pentenylene groups; and linear or branched alkynylene groups having 2 to 10 carbon atoms, such as ethynylene, propynylene, 3-methyl-1-propynylene, butynylene, 1,3-butadiynylene, 2-pentynylene, 2,4-pentadiynylene, 2-hexynylene, 3-heptynylene, and 4-octynylene groups.
[0035] Examples of the divalent alicyclic hydrocarbon group include cycloalkylene groups (including cycloalkylidene groups) having 3 to 18 carbon atoms, such as a 1,2-cyclopentylene group, a 1,3-cyclopentylene group, a cyclopentylidene group, a 1,2-cyclohexylene group, a 1,3-cyclohexylene group, a 1,4-cyclohexylene group, and a cyclohexylidene group.
[0036] Examples of the divalent aromatic hydrocarbon group include C groups such as phenylene (e.g., o-phenylene, m-phenylene, p-phenylene), phenylenebis(methylene) (e.g., 1,2-phenylenebis(methylene), 1,3-phenylenebis(methylene), 1,4-phenylenebis(methylene)), biphenylene, naphthylene, binaphthylene, anthracenylene, phenanthrylene, and fluorene groups. 6-14 An aromatic or non-aromatic heterocycle may be condensed with the benzene ring contained in these groups.
[0037] From the viewpoint of superior processability, it is preferable that the tetracarboxylic dianhydride (A) does not have a spiro carbon atom.
[0038] The molecular weight of the tetracarboxylic dianhydride (A) is, for example, 200 to 1000. The lower limit of the molecular weight is preferably 250. The upper limit of the molecular weight is preferably 900, more preferably 800, further preferably 600, and particularly preferably 500.
[0039] As the tetracarboxylic dianhydride (A), a compound represented by the following formula (2) is preferred from the viewpoint of obtaining a thermoplastic polyimide resin with superior heat resistance and processability, and a molded product with superior light transmittance. [ka]
[0040] [In formula (2), X 2 represents a single bond or a divalent group, R 2 are the same or different and each represents a hydrogen atom or a substituent, and a plurality of R 2 may be bonded to each other to form a ring, and n represents an integer of 0 or more.
[0041] The dashed carbon-carbon bond in the cyclohexane ring in formula (2) indicates that it is either a single bond or a double bond.
[0042] X 2 In the above, the divalent group includes a divalent organic group, an ether bond, a carbonyl bond, an ester bond, etc. The divalent organic group includes the above-mentioned divalent organic group. The divalent organic group is preferably a linear or branched hydrocarbon group (preferably a hydrocarbon group having 1 to 4 carbon atoms) which may have a substituent.
[0043] R 2 Examples of the substituent as R include a hydrocarbon group having 1 to 4 carbon atoms. 2 Examples of the ring formed by bonding of the R include the alicyclic ring, aromatic ring, and heterocyclic ring described above as the ring that can form a condensed ring from the single ring structure. 2 The ring formed by bonding is preferably a 3- to 8-membered ring, more preferably a 3- to 6-membered ring, and further preferably a 5- or 6-membered ring.
[0044] Specific examples of the tetracarboxylic dianhydride (A) include trade name "RIKACID TDA-100" (1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, manufactured by New Japan Chemical Co., Ltd.) and trade name "ENEHYDE" (grades "CpODA", "BzDA", "BNBDA", etc.) (manufactured by ENEOS Corporation).
[0045] (Diamine (B)) The diamine (B) is a compound represented by the following formula (1).
[0046] [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R 1 represents a divalent organic group, and m represents an integer of 0 or more.
[0047] R 1 As the divalent organic group in 2 Examples of the divalent organic group in include those exemplified and explained above, such as a divalent aliphatic hydrocarbon group which may have a substituent, a divalent alicyclic hydrocarbon group which may have a substituent, a divalent aromatic hydrocarbon group which may have a substituent, a divalent group in which two or more of these are bonded, and a divalent group in which two or more of these are bonded via a linking group. Examples of the linking group include an ether bond, an ester bond, a carbonyl bond, and a sulfonyl group.
[0048] R 1From the viewpoint of obtaining a thermoplastic polyimide resin with superior heat resistance, it is preferable that the divalent aromatic hydrocarbon group is a substituted or unsubstituted divalent aromatic hydrocarbon group, and a divalent group in which two or more substituted or unsubstituted divalent aromatic hydrocarbon groups are bonded via a substituted or unsubstituted divalent aliphatic hydrocarbon group or the above-mentioned linking group is preferable. Among them, a divalent group in which two aromatic hydrocarbon groups are bonded via a divalent aliphatic hydrocarbon group or the above-mentioned linking group is particularly preferable. The divalent aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 10 carbon atoms, more preferably an aliphatic hydrocarbon group having 1 to 4 carbon atoms, and even more preferably a dimethylmethylene group.
[0049] R 1 From the viewpoint of providing a thermoplastic polyimide resin with superior heat resistance and processability, the groups represented by the following formulae (1-1) to (1-6) are preferred, the groups represented by the following formulae (1-5) to (1-6) are more preferred, and from the viewpoint of providing a particularly superior processability, the group represented by formula (1-5) is particularly preferred. Note that in formulae (1-1) to (1-6), the bonding positions of the two bonds extending in a wavy line to the benzene ring may be the same or different. Furthermore, the above bond extending in a wavy line is preferably a bond between the phenyl group and X 1 It is preferable that the bond is at the meta or para position relative to the position of bonding to the aryl group. When the bond is at the meta position, the symmetry of the resulting thermoplastic polyimide resin tends to be low and the processability is excellent. When the bond is at the para position, the processability is excellent and the heat resistance is excellent, and the raw material is relatively easy to obtain, so that the thermoplastic polyimide resin can be produced more easily.
[0050] [ka]
[0051] In formula (1), X 1 Among these, an ether bond is preferred.
[0052] In formula (1), m is 0 or more, and is preferably 1 to 3, more preferably 1, from the viewpoint of superior processability.
[0053] In formula (1), the two amino groups are bonded to any of the carbon atoms constituting the phenyl group. The bonding positions of the two amino groups may be the same or different positions relative to each phenyl group. From the viewpoint of obtaining superior processability and heat resistance of the thermoplastic polyimide resin, the bonding positions of the amino groups are preferably selected from X 1 The meta or para position is preferred.
[0054] The molecular weight of the diamine (B) is, for example, 200-600, preferably 250-600, more preferably 300-550, further preferably 350-500, and particularly preferably 350-450.
[0055] The thermoplastic polyimide resin may have a structural unit derived from a tetracarboxylic dianhydride other than the structural unit (A) or a structural unit derived from a diamine other than the structural unit (B). The proportion of the structural unit (A) in the thermoplastic polyimide resin is preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, particularly preferably 90 mol% or more, and may be 95 mol% or more, or 99 mol% or more, based on the total amount (100 mol%) of the structural units derived from the tetracarboxylic dianhydride. The proportion of the structural unit (B) in the thermoplastic polyimide resin is preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, particularly preferably 90 mol% or more, and may be 95 mol% or more, or 99 mol% or more, based on the total amount (100 mol%) of the structural units derived from the diamine.
[0056] The thermoplastic polyimide resin may have a structural unit derived from a dicarboxylic acid or an anhydride thereof (sometimes referred to as "structural unit (C)"). The structural unit (C) seals (caps) unreacted amino groups in the thermoplastic polyimide resin, thereby lowering the reactivity of the thermoplastic polyimide resin and increasing the storage stability.
[0057] Examples of the dicarboxylic acid or anhydride thereof include phthalic acid, phthalic anhydride, 4-chlorophthalic acid, tetrafluorophthalic acid, 2,3-benzophenonedicarboxylic acid, 3,4-benzophenonedicarboxylic acid, cyclohexane-1,2-dicarboxylic acid, cyclopentane-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, etc. Among them, phthalic acid and phthalic anhydride are preferred.
[0058] The amount of the structural unit (C) in the thermoplastic polyimide resin is preferably 0.01 to 4 mol, more preferably 0.1 to 2 mol, based on the total amount (100 mol) of the structural units derived from the tetracarboxylic dianhydride, from the viewpoint of being able to sufficiently cap unreacted amino groups.
[0059] The molar ratio of the structural unit (A) to the structural unit (B) [(A) / (B)] is, for example, 0.7 to 1.3, preferably 0.8 to 1.2, and more preferably 0.9 to 1.1. The molar ratio of the tetracarboxylic dianhydride to the diamine is preferably within the above range.
[0060] The thermoplastic polyimide resin is preferably in the form of a powder. As a result of being in the form of a powder, it has excellent flowability and is easy to process into a film or the like by exerting thermoplasticity. The thermoplastic polyimide resin in the form of a powder may be pelletized. In addition, for example, a polyimide film obtained by a casting method or the like is laminated and pressed under heat to obtain a molded body, and the molded body is cut to produce pellets. However, the pellets obtained tend to generate air bubbles and have poor moldability. On the other hand, the thermoplastic polyimide resin of the present invention has thermoplasticity, so that pellets and molded products can be obtained without causing such problems.
[0061] The glass transition temperature (Tg) of the thermoplastic polyimide resin is preferably 200° C. or higher, more preferably 220° C. or higher, even more preferably 230° C. or higher, and particularly preferably 240° C. or higher. The higher the Tg, the better the heat resistance. The upper limit of the Tg is not particularly limited, but is, for example, 1000° C. The Tg can be measured, for example, by DSC analysis of the powdered thermoplastic polyimide resin.
[0062] The thermoplastic polyimide resin may or may not have a melting point (Tm). When the thermoplastic polyimide resin has a Tm, the Tm is preferably 450°C or less, more preferably 350°C or less. When the Tm is 450°C or less (particularly 350°C or less), the processability is more excellent. From the viewpoint of stably maintaining the powder, the lower limit of the Tm is, for example, 80°C or more, preferably 100°C or more, more preferably 200°C or more, and even more preferably 250°C or more. The Tm can be measured, for example, by DSC analysis of the powdered thermoplastic polyimide resin.
[0063] The 10% weight loss temperature of the thermoplastic polyimide resin is preferably 400° C. or higher, more preferably 450° C. or higher. The higher the 10% weight loss temperature, the more excellent the heat resistance tends to be. The upper limit of the 10% weight loss temperature is, for example, 600° C.
[0064] The melt flow rate (MFR) of the thermoplastic polyimide resin is preferably 10 g / 10 min or more, more preferably 15 g / 10 min or more. When the MFR is 10 g / 10 min or more, the processability is more excellent. Moreover, the MFR is preferably 100 g / 10 min or less, more preferably 80 g / 10 min or less, and even more preferably 50 g / 10 min or less. When the MFR is 100 g / 10 min or less (particularly, 80 g / 10 min or less), the handling property is excellent and the processability is more excellent. The MFR is a value measured using powder or pellets of the thermoplastic polyimide resin under the conditions of a temperature of 337°C and a load of 6.6 kgf.
[0065] [Method of manufacturing thermoplastic polyimide resin] The thermoplastic polyimide resin can be produced by polycondensation reaction of tetracarboxylic dianhydride and diamine. The polycondensation reaction may be carried out in the presence of a solvent. As the solvent, it is preferable to use a solvent in which the thermoplastic polyimide precursor is soluble. Examples of the solvent include aprotic polar solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, N-methylcaprolactam, methyl triglyme, and methyl diglyme; ester solvents such as γ-butyrolactone; ketone solvents such as cyclohexanone, methylcyclohexanone, and methyl ethyl ketone; aromatic hydrocarbon solvents such as toluene and xylene; and phenol solvents such as phenol and cresol. The solvent may be used alone or in combination of two or more.
[0066] The amount of the solvent used is preferably in the range of, for example, 5 to 50% by mass, and more preferably 10 to 40% by mass, such that the non-volatile content concentration becomes, for example, 5 to 50% by mass, and more preferably 10 to 40% by mass.
[0067] The condensation polymerization reaction is preferably carried out in a system that is substantially free of catalysts and curing accelerators such as dehydrating agents, from the viewpoint of easily obtaining a thermoplastic polyimide resin that is excellent in heat resistance and processability and excellent in light transmission. In this specification, "substantially free" means that it is not actively added, except when it is unavoidably present. The amount of the curing accelerator used is preferably 0.0001 parts by mass or less, particularly preferably 0 parts by mass, relative to 100 parts by mass of the total amount of the tetracarboxylic dianhydride and the diamine. Examples of the catalyst include amines other than diamines. Examples of the dehydrating agent include monocarboxylic anhydrides such as acetic anhydride and benzoic anhydride.
[0068] The reaction atmosphere is not particularly limited as long as it does not inhibit the reaction, and may be, for example, an air atmosphere, a nitrogen atmosphere, an argon atmosphere, or the like.
[0069] The reaction temperature is appropriately selected depending on the types of tetracarboxylic dianhydride and diamine, and may be, for example, 40 to 300° C., and preferably 50 to 230° C., and may be performed under reflux of the solvent. The reaction time is, for example, 0.5 to 12 hours, and preferably 1 to 6 hours.
[0070] The thermoplastic polyimide resin and / or thermoplastic polyimide precursor (= polyamic acid) are obtained by the condensation polymerization reaction of the first stage. The thermoplastic polyimide resin and the thermoplastic polyimide precursor are condensation polymers of a tetracarboxylic dianhydride (A) and a diamine (B). The thermoplastic polyimide precursor has an amino group and / or a carboxy group. The reaction liquid obtained by the polycondensation reaction is a composition containing a thermoplastic polyimide precursor, and may further contain a thermoplastic polyimide resin. It is preferable that the composition does not substantially contain the curing accelerator. The content of the curing accelerator in the composition is preferably 0.0001 parts by mass or less, particularly preferably 0 parts by mass, based on 100 parts by mass of the total amount of the tetracarboxylic dianhydride and the diamine.
[0071] The thermoplastic polyimide resin of the present invention cannot be measured by gel permeation chromatography (GPC) because it is insoluble in various solvents, and the thermoplastic polyimide resin is obtained by dehydrating the thermoplastic polyimide precursor, and the molecular weight of the dehydrated water is limited to the molecular weight of the obtained resin, so that the weight average molecular weight (Mw) of the polyimide precursor is hereinafter regarded as the weight average molecular weight (Mw) of the thermoplastic polyimide resin. The weight average molecular weight (Mw) of the thermoplastic polyimide precursor is preferably 5000 to 100000, more preferably 8000 to 70000, and even more preferably 10000 to 50000. When Mw is within the above range, the heat resistance and processability of the thermoplastic polyimide resin are better.
[0072] The thermoplastic polyimide precursor is preferably a fibrous solid. The properties of the thermoplastic polyimide precursor can be adjusted by the raw materials (such as tetracarboxylic dianhydride (A) and diamine (B)) constituting the precursor, the molecular weight, etc. For example, the thermoplastic polyimide precursor can be obtained as a fiber bundle by increasing the reaction temperature of the polycondensation reaction to set the weight average molecular weight to a high value within the above range.
[0073] After the polycondensation reaction is completed, an aging step may be performed. When the aging step is performed, the aging temperature is, for example, about 30 to 60° C., and the aging time is, for example, about 1 to 5 hours. The reaction may be performed by any method such as a batch method, a semi-batch method, or a continuous method.
[0074] After the polycondensation reaction is completed, a terminal blocking agent may be added to block the reactive groups. Examples of the terminal blocking agent include the dicarboxylic acids or their anhydrides. By adding the dicarboxylic acids or their anhydrides, amino groups that may be contained in the thermoplastic polyimide resin or the thermoplastic polyimide precursor can be blocked.
[0075] The above-mentioned capping reaction may be carried out after the reaction product obtained by the above-mentioned polycondensation reaction is separated and purified by general methods such as precipitation, washing, filtration, drying, etc., or may be carried out by adding the above-mentioned end-capping agent to the above-mentioned reaction solution without purification.
[0076] The above-mentioned capping reaction can be carried out in the presence of the above-mentioned solvent. The above-mentioned capping reaction is preferably carried out in a system substantially free of a curing accelerator. The amount of the above-mentioned curing accelerator used is preferably 0.0001 parts by mass or less, particularly preferably 0 parts by mass, based on 100 parts by mass of the total amount of the tetracarboxylic dianhydride and the diamine.
[0077] The amount of the terminal blocking agent added is preferably 0.01 to 4 mol, and more preferably 0.1 to 2 mol, based on 100 mol of the total amount of the tetracarboxylic dianhydride and the diamine.
[0078] The reaction temperature is appropriately selected depending on the type of tetracarboxylic dianhydride and diamine, and is, for example, 100°C or higher, and may be carried out under reflux of the solvent. The reaction time is, for example, 0.5 to 12 hours, preferably 1 to 6 hours. After the reaction is completed, an aging step may be provided. When the aging step is provided, the aging temperature is, for example, about 30 to 60°C, and the aging time is, for example, about 1 to 5 hours. The reaction may be carried out by any method such as a batch method, a semi-batch method, or a continuous method.
[0079] After the polycondensation reaction is completed (after the sealing reaction as necessary), it is preferable to carry out a thermal imidization reaction in which the thermoplastic polyimide precursor is heated to dehydrate it and form an imide ring. The thermal imidization reaction allows a polyimide resin to be obtained as a powder without using a curing accelerator, and the obtained polyimide resin is likely to have thermoplasticity. In addition, the heat resistance and processability are excellent, and the molded product has excellent light transmittance. A thermoplastic polyimide resin is easily obtained.
[0080] The thermal imidization reaction is preferably carried out in a system substantially free of solvent in order to impart thermoplasticity to the polyimide resin obtained and to improve heat resistance and processability. When the polycondensation reaction is carried out in the presence of a solvent, it is preferable to carry out the thermal imidization reaction after volatilizing and removing the solvent after the polycondensation reaction. The amount of solvent used in the thermal imidization reaction is preferably in a range in which the non-volatile concentration is, for example, 90% by mass or more, preferably 95% by mass or more, and particularly preferably 99% by mass or more. For example, it is preferable to remove the solvent after the polycondensation reaction, rinse the remaining monomer components with a suitable solvent such as THF, then add a poor solvent such as methanol to precipitate the thermoplastic polyimide precursor by reprecipitation or the like, dry it, and carry out the thermal imidization reaction on the solid thermoplastic polyimide precursor obtained. By carrying out the drying sufficiently, the imide ring formation can be more sufficiently promoted (the ring closure rate of the thermoplastic polyimide resin is 100%). The drying may be carried out while stirring or breaking up the lumps in order to facilitate the volatilization of the rinsing solvent or poor solvent.
[0081] The thermal imidization reaction is preferably carried out in a system substantially free of the curing accelerator, from the viewpoint of easily obtaining a thermoplastic polyimide resin having excellent heat resistance, processability, and optical transparency. The amount of the curing accelerator used is preferably 0.0001 parts by mass or less, particularly preferably 0 parts by mass, relative to 100 parts by mass of the total amount of the thermoplastic polyimide precursor.
[0082] The reaction atmosphere is not particularly limited as long as it does not inhibit the reaction, and may be, for example, an air atmosphere, a nitrogen atmosphere, an argon atmosphere, or the like.
[0083] The reaction pressure and reaction temperature are appropriately selected depending on the types of tetracarboxylic dianhydride and diamine, and may be performed, for example, under reduced pressure (preferably under vacuum conditions) at a temperature of, for example, 150 to 300° C., preferably 180 to 230° C., under reflux of the solvent. The reaction time is, for example, 1 to 12 hours, preferably 3 to 7 hours.
[0084] After the thermal imidization reaction, an aging step may be carried out. When the aging step is carried out, the aging temperature is, for example, about 30 to 60°C, and the aging time is, for example, about 1 to 5 hours. The reaction can be carried out by any method such as a batch method, a semi-batch method, or a continuous method. In this manner, the powder of the thermoplastic polyimide resin can be obtained.
[0085] The thermoplastic polyimide resin can be used as an adhesive, a heat-resistant modifying filler, a sliding modifying filler, a fiber impregnation resin material, a woven fabric impregnation resin material, a 3D printer resin material, a compression molding material, and the like, in addition to the use as a molded product described later.
[0086] [Molded product] Molded products can be produced using the thermoplastic polyimide resin. The thermoplastic polyimide resin has thermoplasticity and excellent processability, so it is preferable to mold it by a thermoforming method. Examples of the thermoforming method include injection molding, extrusion molding, blow molding, heat press molding, vacuum molding, compressed air molding, laser molding, welding, and welding. In addition, from the viewpoint of suppressing cracking of the molded product and easily obtaining a molded product with excellent light transmission, it is preferable to cool the molded product under gentle conditions after heating.
[0087] The molded article has a light transmittance of at least one of 850 nm, 1310 nm, and 1550 nm (particularly, a light transmittance of at least 1310 nm, more preferably, a light transmittance of three wavelengths) of preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, and particularly preferably 85% or more. The light transmittance is a value measured for a molded article having a thickness of 1 mm.
[0088] Examples of the molded product include a square plate, a film, a sheet, a strand, a pellet, a fiber, a round bar, a square bar, a sphere, a pipe, a tube, a seamless belt, etc. The pellets may be used to prepare other molded products.
[0089] When the molded article has excellent light transmittance, it is preferable that the molded article is used in an optical device. The optical device may be an optical module such as an optical transceiver. The molded article is preferably used in a lens module for the optical device. EXAMPLES
[0090] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.
[0091] Example 1 51.61g (0.125mol) of 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (diamine b1) (molecular weight: 410.52) was dissolved in 210g of NMP (corresponding to an amount with a non-volatile content of 30% by mass) at 60°C under a nitrogen stream, and 38.02g (0.125mol) of tetracarboxylic dianhydride a1 (trade name "Enehyde CpODA", manufactured by ENEOS Corporation) (molecular weight: 294.22) was added, and the reaction was carried out for 3 hours under reflux (boiling point of NMP is 202°C). In order to cap the terminal amine, 0.37g (0.0025mol) of phthalic anhydride (molecular weight 148.12) was added, and the mixture was stirred for another hour and cooled to room temperature. The solution after the reaction was used for gel permeation chromatography measurement described later. After the reaction, 420 g of tetrahydrofuran (THF) was added to the solution, diluted, and reprecipitated with methanol solvent. The solution was filtered, dissolved in THF, and reprecipitated again with methanol. The solution was filtered, and the solvent was removed while drying at 200°C for 5 hours to perform further imidization, to obtain a polyimide resin.
[0092] Example 2 51.68g (0.125mol) of diamine b1 (molecular weight: 410.52) was dissolved in 210g of NMP (corresponding to an amount with a non-volatile content of 30% by mass) at 60°C under a nitrogen stream, and 37.95g (0.125mol) of tetracarboxylic dianhydride a2 (trade name "Rikacid TDA-100", manufactured by New Japan Chemical Co., Ltd.) (molecular weight: 300.27) was added, and the reaction was carried out at 100°C for 3 hours and then at reflux (boiling point of NMP is 202°C) for 2 hours. In order to cap the terminal amine, 0.37g (0.0025mol) of phthalic anhydride (molecular weight 148.12) was added, stirred for another 10 minutes, and cooled to room temperature. The solution after the reaction was used for gel permeation chromatography measurement described later. After the reaction, 420g of THF was added to the solution, diluted, and reprecipitated with methanol solvent. The solution was filtered, dissolved in THF, and reprecipitated again with methanol. The solution was filtered, and the solvent was removed while drying at 200°C for 5 hours to perform further imidization, to obtain a polyimide resin powder.
[0093] Example 3 A polyimide resin powder was prepared in the same manner as in Example 2, except that 0.125 mol of tetracarboxylic dianhydride a3 shown in Table 1 was used as the tetracarboxylic dianhydride.
[0094] The solutions obtained after the reaction in Examples 1 to 3 were reprecipitated with methanol again, and the precipitate was dried to volatilize the solvent, and a solid polyimide precursor was recovered. The polyimide precursor obtained was confirmed to have thermoplastic properties. When the polyimide precursor was pulled, it was easily torn by hand, and it was confirmed that the polyimide precursor was fibrous and was a fiber bundle of a plurality of fibers.
[0095] Examples 4 to 6, Comparative Examples 1 to 6 A polyimide resin powder was prepared in the same manner as in Example 1, except that the compounds shown in Table 1 were used as the tetracarboxylic dianhydride and diamine in an amount of 0.125 mol each.
[0096] The details of each component shown in the table are as follows. (Tetracarboxylic acid dianhydride) a1: Trade name "Enehyde CpODA", manufactured by ENEOS Corporation, a compound represented by the following formula [ka] a2: Trade name "Rikacid TDA-100", manufactured by New Japan Chemical Co., Ltd., 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-C]furan-1,3-dione a3: 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride a4: Product name "Rikacid TMGE-100", manufactured by New Japan Chemical Co., Ltd., a mixture of ethylene glycol bis-anhydrotrimellitate and trimellitic anhydride A5: p-phenylene bis(trimellitate anhydride) a6: a compound represented by the following formula [ka] a7: a compound represented by the following formula [ka] a8: Trade name "TBIS-RXN", manufactured by Taoka Chemical Co., Ltd., a compound represented by the following formula [ka]
[0097] (Diamine) b1: 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) B2: 3,4'-diaminodiphenyl ether B3: 4,4'-diaminodiphenyl ether b4: bis[4-(4-aminophenoxy)phenyl]sulfone B5: m-phenylenediamine
[0098] <Evaluation> The polyimide resins obtained in the examples and comparative examples were evaluated as follows, and the results are shown in Table 1.
[0099] (1) DSC measurement (Tg, Tm) 5 mg of the polyimide resin powder was weighed out, and a differential scanning calorimeter (model number "DSC 3+", manufactured by METTLER TOLEDO) was used to perform DSC measurement under the following temperature conditions to measure Tg and Tm. In Table 1, "-" indicates that no Tm peak was observed. Temperature conditions: 30 degrees for a few minutes. Heat up to 350℃ at 30℃ / min Cool down to 30℃ at -30℃ / min. Heat up to 350℃ at 30℃ / min. Cool down to 30℃ at -30℃ / min. Heat up to 350℃ at 30℃ / min
[0100] (2)10% weight loss temperature 5 mg of polyimide resin powder was weighed out, and the temperature at which the weight had decreased by 10% from the starting weight (10% weight loss temperature) was measured under the following temperature conditions using a simultaneous thermogravimetry and differential thermal analyzer (model number "STA7200RV", manufactured by Hitachi High-Tech Science Corporation). Temperature conditions: Hold at 30 degrees for a few minutes, then raise the temperature to 900 degrees at 10 degrees / min, and hold for a few minutes.
[0101] (3) Imide ring closure rate The imide ring closure rate of the polyimide resin was calculated by the following method. The dried polyimide resin powder was subjected to infrared absorption spectrum measurement using a Fourier transform infrared spectrophotometer (Nicolet iS50, manufactured by Thermo Fisher Scientific) to detect the aromatic ring-derived absorption peak A (1500 cm -1 ) and the imide bond-derived absorption peak B (1780 cm -1 The absorbance of the imide bond was confirmed, and it was confirmed that the aromatic ring-derived absorption peak A had disappeared and the imide bond-derived absorption peak B had been confirmed, indicating that the imide bond had been completely imidized (imide ring closure rate: 100%).
[0102] (4) Pellet moldability The above polyimide resin powder was melt-kneaded in a bench kneader under the following conditions, and pelletized to prepare pellets. The pellet moldability was evaluated according to the following criteria. Tabletop kneader: Circulating tabletop twin-screw kneader (model number "Xplore MC15HT", manufactured by Xplore Instrument) Mixing conditions: Mixing temperature 300°C, screw rotation speed 100 rpm Mixing time: through Supply method: Supply from hopper Pre-drying: 150℃, approx. 8 hours [Evaluation Criteria] 〇: Pellets were produced ×: Not melted and pellets could not be produced
[0103] (5) Formability of test specimen The pellets obtained in the above evaluation of pellet moldability were press-molded into test pieces (100 x 100 x 1 mm) using the following equipment under the following conditions. The moldability of the test pieces was evaluated according to the following criteria. Equipment: 20t manual hydraulic heating press (model number "ICM-4552-4", manufactured by Imoto Manufacturing Co., Ltd.) Conditions: 15g, set temperature 300℃, preheat time 2 minutes, heating load 20kN, pressure time 10s, cooling load 20kN, cooling time 120 seconds or 5 hours, release agent used [Evaluation Criteria] 〇: No cracks were found in the test piece under the condition of a cooling time of 120 seconds. △: Cracks were observed in the test piece with a cooling time of 120 seconds, but no cracks were observed in the test piece with a cooling time of 5 hours. ×: Cracks were observed in the test piece after 5 hours of cooling.
[0104] (6) MFR measurement The pellets obtained in the above evaluation of pellet moldability were dried at 160° C. for 2 hours, and MFR was measured using a Melt Indexer 120FWP (manufactured by Yasuda Seiki Seisakusho Co., Ltd.) under the following measurement conditions. Measurement conditions: temperature 337℃, load 6.6kgf, charge amount 6g
[0105] (7) GPC measurement The solution after the reaction was subjected to gel permeation chromatography (GPC) to measure the weight average molecular weight (Mw). The weight average molecular weight is calculated based on standard polystyrene. The conditions for GPC measurement are as follows: Column: Shodex LF-804, LF-804 connected in series Flow rate: 1.0mL / min Temperature: 40℃ Detection: RID-6A Sample: 20 mg of sample dissolved in 10 mL of tetrahydrofuran
[0106] (8) Light transmittance For the test specimens obtained in the evaluation of the moldability of the test specimens, the light transmittance in the wavelength range of 400 to 2600 nm was measured using a model "UV-3600i" (manufactured by Shimadzu Corporation).
[0107] [Table 1]
[0108] As shown in Table 1, the polyimide resin powders of the Examples were evaluated to have high Tg and excellent heat resistance. In addition, the polyimide resin powders of all the Examples were confirmed to be pelletized by heating, to have thermoplasticity, and were evaluated to have excellent processability. Among them, the moldability of the test pieces of Examples 2 and 3 was superior to that of Example 1, and they were evaluated to have better processability. In addition, a graph showing the relationship between wavelength and light transmittance obtained by measuring the light transmittance of the test pieces of Examples 1 to 3 is shown in FIG. 1. As shown in FIG. 1, the test pieces of Examples 2 and 3 had light transmittance of 80% or more at wavelengths of 850 nm, 1310 nm, and 1550 nm, and were evaluated to have particularly excellent light transmittance.
[0109] On the other hand, when a tetracarboxylic dianhydride having three or less benzene rings and containing an alkyl chain or a benzene ring between ester groups was used (Comparative Examples 1 and 2), it was evaluated as having low Tg and poor heat resistance. When a tetracarboxylic dianhydride having no alicyclic structure and four or more benzene rings was used (Comparative Examples 3 to 5), and when a diamine not corresponding to the compound represented by formula (2) was used (Comparative Example 6), it was evaluated as being difficult to pelletize at 450°C or less and poor processability. The polyimide resins of Comparative Examples 3 to 6 were evaluated as not melting at 450°C or less and possibly not having thermoplasticity.
[0110] Variations of the invention according to the present disclosure are described below. [Appendix 1] A thermoplastic polyimide resin having a structural unit derived from a tetracarboxylic dianhydride (A) having an alicyclic structure and a structural unit derived from a diamine (B) represented by the following formula (1): [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R 1 represents a divalent organic group, and m represents an integer of 0 or more. [Appendix 2] The thermoplastic polyimide resin according to Appendices 1, having a glass transition temperature of 200°C or higher. [Appendix 3] The thermoplastic polyimide resin according to appendix 1 or 2, which is in the form of a powder. [Appendix 4] The thermoplastic polyimide resin according to any one of Appendices 1 to 3, wherein the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded via a single bond or a linking group. [Appendix 5] The thermoplastic polyimide resin according to any one of Appendices 1 to 4, wherein the alicyclic structure is a monocyclic structure having 3 to 6 members. [Appendix 6] R in the above formula (1) 1 6. The thermoplastic polyimide resin according to any one of claims 1 to 5, wherein is a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group. [Appendix 7] A fibrous thermoplastic polyimide precursor which is a condensation polymer of a tetracarboxylic dianhydride (A) having an alicyclic structure and a diamine (B) represented by the following formula (1). [ka] [In formula (1), X 1 indicates a single bond, an ether bond, a carbonyl bond, or an ester bond, and R 1 represents a divalent organic group, and m represents an integer of 0 or more. [Appendix 8] The thermoplastic polyimide precursor according to Appendix 7, wherein the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded via a single bond or a linking group. [Appendix 9] The thermoplastic polyimide precursor according to appendix 7 or 8, wherein the alicyclic structure is a monocyclic structure having 3 to 6 members. [Appendix 10] R in the above formula (1) 110. The thermoplastic polyimide precursor according to any one of claims 7 to 9, wherein is a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group. [Appendix 11] A composition comprising the thermoplastic polyimide precursor according to any one of Appendices 7 to 10, and substantially free of a curing accelerator. [Appendix 12] A molded product of the thermoplastic polyimide resin according to any one of Appendices 1 to 6. [Appendix 13] An optical device comprising the molded article according to appendix 12.
Claims
1. A thermoplastic polyimide resin having a structural unit derived from a tetracarboxylic dianhydride (A) having an alicyclic structure and a structural unit derived from a diamine (B) represented by the following formula (1): 【Chemistry 1】 [In formula (1), X 1 represents a single bond, an ether bond, a carbonyl bond, or an ester bond; R 1 represents a divalent organic group, and m represents an integer of 0 or more.
2. 2. The thermoplastic polyimide resin according to claim 1, which has a glass transition temperature of 200° C. or higher.
3. 3. The thermoplastic polyimide resin according to claim 1, which is in the form of a powder.
4. 3. The thermoplastic polyimide resin according to claim 1, wherein the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded to each other via a single bond or a linking group.
5. 3. The thermoplastic polyimide resin according to claim 1, wherein the alicyclic structure is a monocyclic structure having 3 to 6 members.
6. R in the formula (1) 1 3. The thermoplastic polyimide resin according to claim 1, wherein R is a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group.
7. A fibrous thermoplastic polyimide precursor which is a condensation polymer of a tetracarboxylic dianhydride (A) having an alicyclic structure and a diamine (B) represented by the following formula (1): 【Chemistry 1】 [In formula (1), X 1 represents a single bond, an ether bond, a carbonyl bond, or an ester bond; R 1 represents a divalent organic group, and m represents an integer of 0 or more.
8. 8. The thermoplastic polyimide precursor according to claim 7, wherein the tetracarboxylic dianhydride (A) has a cyclic acid anhydride structure, and the alicyclic structure and at least one of the cyclic acid anhydride structures are bonded to each other via a single bond or a linking group.
9. The thermoplastic polyimide precursor according to claim 7 or 8, wherein the alicyclic structure is a monocyclic structure having 3 to 6 members.
10. R in the formula (1) 1 9. The thermoplastic polyimide precursor according to claim 7 or 8, wherein is a divalent group in which two aromatic hydrocarbon rings are bonded via a dimethylmethylene group.
11. A composition comprising the thermoplastic polyimide precursor according to claim 7 or 8, and substantially free of a curing accelerator.
12. A molded product of the thermoplastic polyimide resin according to claim 1 or 2.
13. An optical device comprising the molded article according to claim 12.
Citation Information
Patent Citations
Method for producing thermoplastic polyimide
JP2002293930A
Extraction method and device for implementing such method
WO1983000442A1